Concussion Management for the Orthopaedic Surgeon. Issue 11 (November 2020) - Jildeh, Toufic R.; Shkokani, Lina; Meta, Fabien; Tramer, Joseph S.; Okoroha, Kelechi R.
Abstract : Orthopaedic surgeons functioning as team physicians are in a unique position to recognize subtle changes in an athlete's behavior and may be the first responders to concussions at sporting events. The rate of sports-related concussions has increased over the past few decades, necessitating that orthopaedic team physicians gain a greater understanding of the diagnosis and management of this condition. During the sideline evaluation, life-threatening injuries must be ruled out before concussion evaluation may take place. In most cases, patients experience a resolution of symptoms within a week; however, a smaller subset of patients experience persistent symptoms. Physicians covering sporting events must remain current regarding recommendations for treating sports-related concussions and must document their management plan to minimize potential harm to an athlete.